2000
DOI: 10.1155/2000/642707
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Hepatitis C Burden in Canada

Abstract: To assess the risk of hepatitis C in Canada and to predict the burden that this disease may pose to the Canadian society in the near future, expected numbers of persons at different stages of the disease currently and in the next decade were estimated by simulation using a published hepatitis C natural history model with no treatment effect being applied. Based on the estimate of 240,000 persons who are currently infected with the hepatitis C virus in Canada, the simulation analysis demonstrated that the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 14 publications
2
45
0
5
Order By: Relevance
“…The relatively low overall prevalence of anti-HCV antibodies (1.3%) among Libyans is still higher than Canada (0.8%), Australia (1.1%) and some western European countries including France (1.1%) and Germany (0.6%) [13][14][15][16][17] and is close to that reported from large studies of the general population in the United States of America (1.8%-2.2%) [18][19][20][21] and much lower than the figures reported for Pakistan (5%-7%) [22,23] and Egypt (22%) [24], a neighbouring country with a high movement of workers every year. The results of this study also are consistent with previously published studies of selected Libyan populations [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 97%
“…The relatively low overall prevalence of anti-HCV antibodies (1.3%) among Libyans is still higher than Canada (0.8%), Australia (1.1%) and some western European countries including France (1.1%) and Germany (0.6%) [13][14][15][16][17] and is close to that reported from large studies of the general population in the United States of America (1.8%-2.2%) [18][19][20][21] and much lower than the figures reported for Pakistan (5%-7%) [22,23] and Egypt (22%) [24], a neighbouring country with a high movement of workers every year. The results of this study also are consistent with previously published studies of selected Libyan populations [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 97%
“…1 Prediction models of the future HCV-related burden of illness in Canada suggest that approximately 4,000 new HCV infection cases are expected each year. 10 Estimates propose that the number of patients with HCV-related cirrhosis, liver failure, and hepatocellular carcinoma will likely double by the year 2008; simultaneously, it is expected that the number of HCV-related liver deaths would more than double in that period. 1,9,10 The HCV-related health care costs have been estimated at $500 million per annum in Canada to date; by 2010, this cost burden is expected to reach $1 billion (M. Krajden, personal communication, 2002).…”
Section: General Populationmentioning
confidence: 99%
“…10 Estimates propose that the number of patients with HCV-related cirrhosis, liver failure, and hepatocellular carcinoma will likely double by the year 2008; simultaneously, it is expected that the number of HCV-related liver deaths would more than double in that period. 1,9,10 The HCV-related health care costs have been estimated at $500 million per annum in Canada to date; by 2010, this cost burden is expected to reach $1 billion (M. Krajden, personal communication, 2002). Similar proportions of the burden of illness related to HCV exists for the United States, where 2.7 million persons have chronic HCV infection; for the period 2010-2019, estimates predict 165,000 deaths from liver disease, 27,000 deaths from hepatocellular carcinoma, $10.7 billion in direct medical expenditures, and societal costs of $75.5 billion in lost productivity related to HCV.…”
Section: General Populationmentioning
confidence: 99%
“…These include hepatitis C (HCV) and hepatitis B virus (HBV) infection, haemochromatosis, alcoholic cirrhosis and other causes of chronic liver disease that result in cirrhosis. 3 8,20 Despite the Canadian data indicating that hepatitis C is likely responsible for a substantial proportion of the increase in incidence and mortality, chronic infection with the hepatitis B virus remains the best known and most important risk factor for HCC worldwide. 8,21 It has been estimated that globally, 80% of HCC cases is due to HBV.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 Based on the number of current cases of HCV in Canada, one study predicted that by 2008, the number of patients with cirrhosis caused by hepatitis C would increase by 92%, based on the estimate that 240 000 persons are currently infected with HCV in Canada. 17,18,20 One study also suggested that the number of HCC cases related to hepatitis C would also increase by 102% in the next 10 years. 20 Other results from the risk factor data for HCC, suggest that a further increase in HCC in Canada is likely.…”
Section: Discussionmentioning
confidence: 99%